KEBERAGAMAN BUDAYA INDONESIA - Tony Sugianto, (TANDA: Jurnal Kajian Budaya, Bahasa dan Sastra (e-ISSN: 2797-0477), 2023)
Indonesia is an archipelagic country with more than 17,000 islands and a rich diversity of ethnic groups. This scholarly work aims to explore various aspects of Indonesian culture, including language, customs, arts, and traditions, as well as the challenges faced in their preservation. This study employs a qualitative approach using literature review and observational methods. The findings indicate that Indonesia’s cultural diversity is an invaluable asset, yet it requires continuous and sustainable preservation efforts.